The political sacred and the holiness of life itself - Flood, G (Routledge, 2017)
This article reflects on Agamben’s formulation of the sacred within the political order of the West, contrasting this with the Durkheim/Bellah view of the sacred/profane opposition, and then presenting two arguments that reduction of the sacred to the political is insufficient, one a form of biological reductionism that seeks to locate the sacred within the common, biological nature of human life itself, the other an abductive argument for human transformation in terms of what Sloterdjik has called ‘vertical tension.’ This argument turns out to be one for locating holiness in the very notion of life itself that I wish to ground in the idea of social cognition.